2018
DOI: 10.1037/lhb0000273
|View full text |Cite
|
Sign up to set email alerts
|

Police managers’ self-control and support for organizational justice.

Abstract: Recent policing research has identified a positive relationship between line-level officers' perceptions of organizational justice and their adherence to agency goals and job satisfaction. However, we have little understanding of the factors that are related to police managers' support for organizational justice when interacting with employees. We collected survey data from a sample of U.S. command-level officers (N = 211) who attended a training program in a southern state to address this gap in the literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…These are the very officers who are in a position to use organizational justice to the benefit of their subordinate officers. Supervisors who have been negatively affected by Ferguson and similar controversies may be at a disadvantaged spot to ensure effective managerial strategies like employing organizational justice (see Wolfe, Nix, and Campbell, 2018). The present study attempted to shed some light on this matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are the very officers who are in a position to use organizational justice to the benefit of their subordinate officers. Supervisors who have been negatively affected by Ferguson and similar controversies may be at a disadvantaged spot to ensure effective managerial strategies like employing organizational justice (see Wolfe, Nix, and Campbell, 2018). The present study attempted to shed some light on this matter.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that it would be wise to focus attention on building audience legitimacy. As discussed above, an internal mechanism that could help in this process would be for police supervisors to ensure organizational justice when dealing with subordinates (see also, Wolfe et al ., 2018). Line-level officers who are treated fairly by their superiors are more likely to treat the public in the same manner (Tankebe, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The specific categories were very small ( n < 25), small ( n < 50), medium ( n < 100), large ( n < 500), and very large ( n ≥ 501) categories based on the number of sworn officers reported by the participant. The decision to include these control variables was based on prior empirical research and not based on theoretical rationale (Murphy, 2009; Reynolds & Helfers, 2018; Wolfe & Nix, 2016; Wolfe, Nix, & Campbell, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…By contemplating the possibilities of this perspective, we aim to make two contributions to this literature. First, research on justice enactment has identified both situational factors (e.g., Monin, Noorderhaven, Vaara, & Kroon, 2013;Sherf, Venkataramani, & Gajendran, in press;Wo, Ambrose, & Schminke, 2015) and individual factors (e.g., Brebels, De Cremer, van Dijke, & Van Hiel, 2011;Patient & Skarlicki, 2010;Qin, Ren, Zhang, & Johnson, 2017;Scott et al, 2014;Wolfe, Nix, & Campbell, 2018) that guide agents' behavior. Despite the fact that these findings may help us better understand justice violations, we maintain that they will not entirely eliminate them because trade-offs between competing interests are inherent to many justice-related decisions.…”
Section: Thanos Avengers: Infinity Warmentioning
confidence: 99%